2010
DOI: 10.1021/jf904343f
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Oxidation in Algae Oil-in-Water Emulsions Stabilized by Bovine and Caprine Caseins

Abstract: Caseins (alpha(s1)-, alpha(s2)-, and beta-casein) are phosphoproteins that are capable of binding transition metals and scavenging free radicals; this property makes them good candidates to be used as natural antioxidants in oil-in-water emulsions. Caprine casein exhibits variability in alpha(s1)-casein content generated by genetic polymorphism. This variability in composition could lead to altered antioxidant properties. Thus, the ability of two caprine caseins differing in alpha(s1)-casein content to inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 54 publications
(68 reference statements)
0
32
0
Order By: Relevance
“…One factor contributing to the differences in antioxidant activity of the bovine and caprine caseins in algae oil‐in‐water emulsions is the different profile of caseins (Mora‐Gutierrez et al ., ). Bovine and caprine caseins both contain the four main casein classes: α s1 ‐, α s2 ‐, β‐ and κ‐casein, but the level of α s1 ‐casein in caprine caseins isolated from the milks of American‐bred, French‐Alpine goats ranges from high to low (Mora‐Gutierrez et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…One factor contributing to the differences in antioxidant activity of the bovine and caprine caseins in algae oil‐in‐water emulsions is the different profile of caseins (Mora‐Gutierrez et al ., ). Bovine and caprine caseins both contain the four main casein classes: α s1 ‐, α s2 ‐, β‐ and κ‐casein, but the level of α s1 ‐casein in caprine caseins isolated from the milks of American‐bred, French‐Alpine goats ranges from high to low (Mora‐Gutierrez et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Because of the compositional differences, these milk proteins exhibit major differences ( P < 0.05) in terms of the content of potential antioxidative amino acids histidine, methionine, phenylalanine, proline, tryptophan and tyrosine (Fig. ); curiously, these differences favour the bovine casein, which in previous studies was less effective in suppressing lipid oxidation (Mora‐Gutierrez et al ., ). It was expected that a high content of antioxidative amino acids in the caseins would lead to a decrease in lipid oxidation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Hydroperoxide, an initial product of lipid oxidation degrades causing volatiles like aldehydes and alcohols that cause rancidity (Kim et al 2007;Min and Boff 2002). Oxidation of lipids can occur when exposed to light, air, transition metals, and elevated temperatures (Harris 2007;Mora-Gutierrez et al 2010). A study on the stability of biodiesel from sunflower oil demonstrated that increases were measured in acid and peroxide content for storage temperatures of 50°C and in the presence of light (Du Pleiss et al 1985).…”
Section: Lipid Stability During Harvest and Dewateringmentioning
confidence: 99%